Abnormalities of tetrahydrobiopterin metabolism - Hoffmann, Georg F.; Kuseyri Hübschmann, Oya (MedLink neurology, 2023)
Tetrahydrobiopterin (BH4) deficiencies result in insufficient synthesis of the monoamine neurotransmitters dopamine and serotonin, and may present with hyperphenylalaninemia (HPA). Defects of BH4 metabolism comprise a group of treatable pediatric neurotransmitter disorders. Without early diagnosis…
Gesehen am 31.08.2023